Edukasi Pemberian Makanan Pendamping Air Susu Ibu (MP ASI) di Dusun Pulau Payung - Miftahurrahmi Miftahurrahmi; Sriwidya Astuti Khati (Nusantara Mengabdi Kepada Negeri, 2026)
Complementary feeding (MP-ASI) is needed because breastmilk alone is no longer able to meet the increasing nutritional needs of babies as they grow older. Complementary feeding (MP-ASI) is crucial for meeting children's nutritional needs. Proper complementary feeding practices can prevent malnutrition in children. This Community Service (PKM) was implemented to increase public knowledge, especially among mothers with babies, about exclusively breastfeeding their babies and providing complementary feeding after 6 months of age. This Community Service activity was carried out in the form of health education. The health education method used lectures and interactive discussions. The strategic target was mothers with babies aged 0-2 years in Pulau Payung Hamlet in 2026. Almost all mothers with babies invited to this activity attended. This education has increased knowledge among mothers with babies about providing complementary feeding. Therefore, mothers now understand and know the appropriate time to provide complementary feeding to their babies, the type of complementary feeding to be given, and the timing of the complementary feeding.